Analisis Perbandingan Efektivitas QRIS dengan Metode Pembayaran Digital Lainnya pada Generasi Muda di Kota Surakarta terhadap Minat Pengguna Pembayaran Digital - Rhevan Bardiaman; Dika Puspitaningrum (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to analyze the effectiveness of QRIS compared to other digital payment methods among young people in Surakarta City in terms of their interest in digital payments, by applying the Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology 2, and Innovation Diffusion Theory frameworks. The study uses a quantitative approach, involving a sample of 125 young people who use digital payments in Surakarta City. Information was obtained through questionnaires and processed using multiple linear regression analysis. The research findings reveal that all independent variables were found to significantly influence the interest of digital payment users. However, comparatively, other digital payment methods (X2) were found to have a slightly stronger influence than QRIS (X1).